Design and Preparation of Molecularly Imprinted Membranes for Selective Separation of Acteoside - Zhao, Xiaobin (Front Chem, 2020)
Acteoside (ACT) belongs to a type of phenylethanoid glycosides (PhGs), and it is worthy of obtaining high-purity due to its significant medicinal functions. In this study, a novel class of MIMs was designed and synthesized with PVDF membranes as the base membrane for high selective separation and enrichment of ACT. The effects of the different functional monomers, the amounts of functional monomers, crosslinking agents, and initiators on the separation properties of MIMs were investigated. Furthermore, adsorption ability, permeation capacity, and reusability of MIMs were discussed for ACT. It indicated that MIM7 was the optimal performance of MIMs. The adsorption ability of MIM7 for ACT was 62.83 mg/g, and the selectivity factor (α) of MIM7 was up to 2.74 and its permeability factor (β) was greater than 2.66. Moreover, the adsorption amount of MIM7 was still more than 88.57% of the initial value after five cycles. As an ACT imprinted layer of MIMs only had recognition sites for ACT molecules, which recombined with the recognition sites in the membrane permeation experiment, ACT molecules penetration was hindered. However, the analogs of ECH successfully passed MIMs. It indicated that the selective MIMs for ACT followed the mechanism of delayed permeation. This work provides an important reference for the high permselective separation of natural products.